Analysis of The English Learning Process in Islamic Elementary Boarding Schools - Dariyanto, Dariyanto; Farhana, Husna; Gumala, Yosi; Syaodih, Ernawulan (Jurnal Basicedu, 2022)
This study objectives to designate the English learning of elementary school (SD) students in the Al-Multazam boarding school. English as a foreign language is taught to teach the basics of English. Curriculum design to formulate students who have Rudimentary English skills. The type of research used in this investigation is qualitative research. Data collection methods used are: observation, interviews and documentation. From observations and interviews, it is decided that students' English learning in boarding schools is still very unpretentious. The teachers have not encountered the educational levels and qualifications, especially English. Learning English is not only carried out formally (face to face) but language programs: vocabulary delivery, morning conversation, and performances in student activities are a form of intensive language learning at the Al-Multazam boarding school. Evaluation of learning for English is carried out with an oral and written examination model every semester as a form of mentality and academic assessment of Al-Multazam students' language skills